Ongoing search for diagnostic biomarkers in idiopathic normal pressure hydrocephalus. (December 2009) - Tarnaris, Andrew; Toma, Ahmed K; Kitchen, Neil D; Watkins, Laurence D
Idiopathic normal pressure hydrocephalus is a syndrome, which typically has a clinical presentation of gait/balance disturbance, often accompanied by cognitive decline and/or urinary incontinence. Its diagnosis is based on relevant history and clinical examination, appropriate imaging findings and physiological testing. The clinical picture of idiopathic normal pressure hydrocephalus may occasionally be difficult to distinguish from that of Alzheimer''s dementia, subcortical ischemic vascular dementia and Parkinson''s disease. The aim of this article is to systematically review the literature from the last 29 years in order to identify cerebrospinal fluid (CSF) or imaging biomarkers that may aid in the diagnosis of the syndrome. The authors concluded that no CSF or imaging biomarker is currently fulfilling the criteria required to aid in the diagnosis of the condition. However, a few studies have revealed promising CSF and imaging markers that need to be verified by independent groups. The reasons that the progress in this field has been slow so far is also commented on, as well as steps required to apply the current evidence in the design of future studies within the field.